MOTIF MERANTAU DALAM KABA - Haris Septian (Jurnal Elektronik WACANA ETNIK, 2017)
This article describes the motives of Minangkabau people to merantau in kaba. Through intrinsic analysis, the analysis of kaba was continued using the socio-literary approach based on the sociology of the Minangkabau communityThe motive of merantau in kaba are (1) cultural factors, (2) economic factors, (3) deepening knowledge, (4) social factors, and (5) accompanying the husband. The professionals involved in the majority are trading. The area that is the destination of nomads is cities with a high level of the trade such as the City of Bukittinggi, the City of Padang, and the City of Medan.